1979
DOI: 10.7326/0003-4819-91-2-194
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Coagulation Disorders in Chlorpromazine-Treated Patients

Abstract: The prevalence of immunologic and coagulation disorders in 75 schizophrenic patients treated with chlorpromazine or other antipsychotic drugs was evaluated. Four groups were studied: Group A, chlorpromazine treatment for more than 2 1/2 years; Group B, chlorpromazine and other antipsychotic drug treatment for more than 2 1/2 years; Group C, chlorpromazine treatment for less than 2 1/2 years; Group D, no chlorpromazine, but other antipsychotic drug treatment. Significant elevation of serum IgM and prolongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(56 citation statements)
references
References 24 publications
1
54
0
1
Order By: Relevance
“…80,81 Spivak et al 63 found that, in the group of schizophrenic patients who had never received psychotropic medication (n = 20), total hemolytic activity was significantly lower than in healthy controls (n=37). Nevertheless, no statistical differences were observed between haloperidol-treated (n = 34) versus drug-free (n=37) and haloperidol-and never-treated schizophrenic patient groups.…”
Section: The Influence Of Psychiatric Medicationmentioning
confidence: 99%
“…80,81 Spivak et al 63 found that, in the group of schizophrenic patients who had never received psychotropic medication (n = 20), total hemolytic activity was significantly lower than in healthy controls (n=37). Nevertheless, no statistical differences were observed between haloperidol-treated (n = 34) versus drug-free (n=37) and haloperidol-and never-treated schizophrenic patient groups.…”
Section: The Influence Of Psychiatric Medicationmentioning
confidence: 99%
“…Appearance of the inhibitor has been associated with a number of drugs, such as penicillin and notably chlorpromazine, where therapy leads to the development of a number of immunological abnormalities (Zarrabi et al, 1979). There is no previous report ofthe lupus anticoagulant with Fansidar administration.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion was initially proposed in the 1980's, in response to a high prevalence of aPL antibodies in antipsychotics users (Zarrabi et al, 1979;Canoso & Sise, 1982;Canoso & de Oliveira, 1988;Canoso et al, 1990;Lillicrap et al, 1990;Davis et al, 1994;Kanjolia et al, 1997;Vargas-Alarcon et al, 1997;Schwartz et al, 1998Schwartz et al, , 1999Schwartz et al, , 2009. Then it was speculated that this association could depend on antipsychotics type, asother observational series showed an increase in the prevalence of aPL antibodies in chlorpromazine users compared with users of other antipsychotics (Zarrabi et al, 1979;Canoso & de Oliveira, 1988).…”
Section: Abstract: Antiphospholipid Antibodies Antipsychoticsmentioning
confidence: 99%